FUNGSI PENGAWASAN DEWAN PERWAKILAN DAERAH KABUPATAN KUANTAN SINGINGI TERHADAP PERATURAN DAERAH NOMOR 7 TAHUN 2012 TENTANG RETRIBUSI PELAYANAN PASAR DI KABUPATEN KUANTAN SINGINGI - HIDAYATUL QONITA NAFRIAL; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Given the importance of implementing regional autonomy, the government makes the market a priority program to increase income and also economic welfare for the community. Therefore, the Kuantan Singingi Government makes the market one of the potential sources of regional income. Kuantan Singingi has 12 traditional markets located throughout the Kuantan Singingi Regency which are managed by the local government and 34 village markets managed by the village government. This thesis discusses the supervisory function of the Regional Representative Council of Kuantan Singingi Regency against Regional Regulation Number 7 of 2012 concerning Market Service Retribution in Kuantan Singingi Regency.This type of research can be classified in the type of sociological legal research, or called field research, namely examining the applicable legal provisions and what is happening in reality in society. The research location is at the Regional Revenue Agency Office of Kuantan Singingi Regency and is carried out at the Market in Kuantan Singingi Regency. Sources of data used, namely: primary data and secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques in this study were interviews and literature study. Data analysis was carried out qualitatively, namely the data obtained not using statistics or mathematics or the like.The conclusion of this study is that the supervisory function of the Regional House of Representatives of Kuantan Singingi Regency against Regional Regulation Number 7 of 2012 concerning Market Service Retribution in Kuantan Singingi Regency has not implemented a systematic monitoring mechanism. Obstacles to supervision activities against Regional Regulation Number 7 of 2012 concerning Market Service Fees in Kuantan Singingi Regency are the laws that have been formed and agreed upon are not implemented properly, the ineffective communication and coordination between the executive and the legislature at the Kuantan Singingi Regency Regional Level and cultural factors The law is the supervision by the Kuantan Singingi Regency DPRD as the essence of the control function of the legislative body. Efforts to supervise the Regional People's Representative Council of Kuantan Singingi Regency are to effectively implement the law that has been formed and agreed upon, the executive and the legislature at the Regional Level of Kuantan Singingi Regency communicate and coordinate, so that effective law enforcement is realized and the third legal culture effort is the legislature. and executives should work together in administering the local government of Kuantan Singingi Regency. The writer's suggestion is that the DPRD is expected to be able to play its role optimally in carrying out the control function on the management of the Kuantan Singingi Regency Market Retribution.Keywords: Supervision Function - Regional Representative Council of Kuantan Singingi Regency - Market Service Retribution.